Expert System for Early Detection of Disease in Corn Plant Using Naive Bayes Method: Expert System for Early Detection of Disease in Corn Plant Using Naive Bayes Method - Budianto Budianto; Iskandar Fitri; Winarsih Winarsih (Institute of Computer Science (IOCS), 2020)
Corn is a third main plant after the paddies and squeeze in the world, and occupied a second position after the paddies in indonesia. Corn grows both good in the hot areas and cold with the rainfall and irrigation. But it's often dealing with a corn peasants Other than the pest is less information about the disease that attacked corn plants so that cause productivity becomes reduced. The expert - based expert system that has been built with framework php is the codeigniter and MySQL As the databases and methods used in detecting initial disease on the corn plant is Naïve Bayes. The result in the probation is a prodial by a disease on the corn plant is being used as a probe for decision for the farmers'decision. The system that has been built is expected to help the peasants in determine and Choose the right handling and according to the level of 92% of the system.